Social Support as Psychological Survival Among Persons Deprived of Liberty: An Interpretative Phenomenological Analysis - Wong, Jay; Matic, Andreya; Pasague, Jude Wilbern; Dominguez, Jemerson (JPAIR Multidisciplinary Research, 2026)
Persons deprived of liberty experience persistent psychological stressors, including social isolation, loss of autonomy, and restricted interpersonal contact. While social support is widely recognized as a protective factor for mental health, existing literature largely assumes its accessibility and stability—conditions that are often absent in correctional settings. This study reconceptualizes social support as a survival-oriented process shaped by structural constraints within incarceration. Using a qualitative design, in-depth semi-structured interviews were conducted with twelve incarcerated individuals in a Philippine detention facility. Data were analyzed through Interpretative Phenomenological Analysis to capture how participants make sense of their experiences. Findings revealed four interrelated themes: (1) social support as emotional survival, (2) selective trust and guarded relationships, (3) institutional constraints on support-seeking, and (4) resilience through limited but meaningful connections. The findings suggest that social support in incarceration is not merely a buffering resource but a survival-oriented and dynamically negotiated system embedded within structural limitations. This study advances the concept of a constrained social support ecology, highlighting how support is selectively reconstructed and accessed within restrictive detention environments. The findings contribute to correctional mental health literature by reframing social support as a psychologically adaptive survival process rather than a consistently available protective resource. Practical implications highlight the need for correctional policies and psychosocial interventions that strengthen meaningful social connections, peer support systems, and family communication as foundations for psychological survival, rehabilitation, and reintegration among persons deprived of liberty.